NSOM Lithography for Organized Growth of Gap Nanowires - Ivana Lettrichova; Dusan Pudis; Agata Laurencikova; Stanislav Hasenohrl; Jozef Novak; Jaroslava Skriniarova (Communications - Scientific letters of the University of Zilina, 2014)
In this contribution, near field scanning optical microscope (NSOM) lithography is presented as a tool for organized growth of nanowires. Non contact mode of NSOM lithography was used to pattern planar structures in photoresist deposited on GaP substrate. In combination with lift-off technique, metal-catalyst particles on GaP substrate for subsequent growth of GaP nanowires were prepared. Different periodic and predefined arrangements of GaP nanowires were achieved.